Assessment of distribution of ventilation by electrical impedance tomography in standing horses. (29th December 2015) - Ambrisko, T D; Schramel, J P; Adler, A; Kutasi, O; Makra, Z; Moens, Y P S
Abstract: The aim was to evaluate the feasibility of using electrical impedance tomography (EIT) in horses. Thoracic EIT was used in nine horses. Thoracic and abdominal circumference changes were also measured with respiratory ultrasound plethysmography (RUP). Data were recorded during baseline, rebreathing of CO2 and sedation. Three breaths were selected for analysis from each recording. During baseline breathing, horses regularly took single large breaths (sighs), which were also analysed. Functional EIT images were created using standard deviations (SD) of pixel signals and correlation coefficients (R) of each pixel signal with a reference respiratory signal. Left-to-right ratio, centre-of-ventilation and global-inhomogeneity-index were calculated. RM-ANOVA and Bonferroni tests were used ( P < 0.05). Distribution of ventilation shifted towards right during sighs and towards dependent regions during sighs, rebreathing and sedation. Global-inhomogeneity-index did not change for SD but increased for R images during sedation. The sum of SDs for the respiratory EIT signals correlated well with thoracic ( r 2 = 0.78) and abdominal ( r 2 = 0.82) tidal circumferential changes. Inverse respiratory signals were identified on the images at sternal location and based on reviewing CT images, seemed to correspond to location of gas filled intestines. Application of EIT in standing non-sedated horses is feasible. EIT images may provide physiologically useful information even in situations, such as sighs, that cannot easily be tested by other methods.